Morphogenetic and phenological changes in phenolic content of Hypericum leptophyllum, an endemic Turkish species. Issue 2 (2nd April 2016) - Seyis, Fatih; Radusiene, Jolita; Ivanauskas, Liudas; Jakstas, Valdas; Cirak, Cuneyt
Abstract : The present study was conducted to determine the morphogenetic and phenologic variations in the content of the main bioactive compounds in Hypericum leptophyllum Hochst., an endemic species from Turkish flora. Wild plants were harvested at five phenological stages: vegetative, floral budding, full flowering, fresh fruiting, and mature fruiting, and assayed for chemical content by HPLC. Results indicated that H. leptophyllum did not accumulate hypericin, pseudohypericin, hyperforin, and adhyperforin. The phenolic content in whole plants increased generally during plant phenology and higher accumulation levels were observed at flowering. Among the reproductive organs, amentoflavone, quercetin, avicularin, and hyperoside contents were the highest in floral buds (2.09, 2.18, 0.55, and 2.62 mg g −1 dry mass (DM), respectively). Leaves harvested at the floral budding stage produced the highest content of chlorogenic acid, neochlorogenic acid, caffeic acid, and isoquercetin (53.32, 6.25, 0.03, and 1.91 mg g −1 DM, respectively), while leaves of plants at the vegetative stage of plant development accumulated the highest content of 2, 4-dihydroxybenzoic acid and quercitrin (0.29 and 0.54 mg g –1 DM, respectively). This is the first report of the presence of avicularin, rutin, (+)-catechin, (–)-epicatechin, amentoflavone, caffeic acid, neochlorogenic acid, and 2, 4-dihydroxybenzoic acid in this species. Such data could be useful for the evaluation of new sources of bioactive compounds, as well as for increasing phytotaxonomic knowledge for the poorly studied Hypericum species.